2024
DOI: 10.1186/s12979-024-00414-7
|View full text |Cite|
|
Sign up to set email alerts
|

The interplay between obesity, immunosenescence, and insulin resistance

Ghazaleh Shimi,
Mohammad Hassan Sohouli,
Arman Ghorbani
et al.

Abstract: Obesity, which is the accumulation of fat in adipose tissue, has adverse impacts on human health. Obesity-related metabolic dysregulation has similarities to the metabolic alterations observed in aging. It has been shown that the adipocytes of obese individuals undergo cellular aging, known as senescence. Senescence can be transmitted to other normal cells through a series of chemical factors referred to as the senescence-associated secretory phenotype (SASP). Most of these factors are pro-inflammatory compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Evidence from numerous investigations has shown that elevated levels of reactive oxygen species (ROS) in the bloodstream resulting from deposited fat have been linked to activating insulin resistance (IR) in various adipose tissues and skeletal muscles [ 58 , 61 ]. IR is a common feature of type 2 diabetes, and resistance occurs long before the onset of the disease.…”
Section: Recent Advances In Understanding Dietary Anthocyanins’ Anti-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from numerous investigations has shown that elevated levels of reactive oxygen species (ROS) in the bloodstream resulting from deposited fat have been linked to activating insulin resistance (IR) in various adipose tissues and skeletal muscles [ 58 , 61 ]. IR is a common feature of type 2 diabetes, and resistance occurs long before the onset of the disease.…”
Section: Recent Advances In Understanding Dietary Anthocyanins’ Anti-...mentioning
confidence: 99%
“…In diabetic patients, daily supplementation with 320 mg of ACNs was found to inhibit the expression of proinflammatory factors related to NF-κB pathways, including TNF-α, IL-6, and IL-18 [ 71 ]. At the cellular level, the activated transcription factor NF-κB induced the activity of TNF-α and the interleukins, thereby altering insulin sensitivity [ 46 , 61 ]. Therefore, the use of anthocyanin, which has been shown to have positive effects on the process of inflammation, may contribute to the development of treatment approaches focused on inhibiting NF-κB.…”
Section: Clinical Studies On Anthocyanin Interventions—an Update From...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported a typo found in the graphical abstract, the word “inflamation “ needs to be corrected to “inflammation “. The corrected graphical abstract is presented below.…”
mentioning
confidence: 99%